How the congruence between public servants’ schemas and legal legitimacy affects top-down public policy implementation - Souza, Jeferson Tadeu de; Rossoni, Luciano (Frontiers in Sociology, 2025)
Why do some public policies mandated by the highest levels of government succeed, while others fail? This essay offers a partial answer by proposing that the effectiveness of a public policy depends on the congruence between the legal legitimacy of the law that establishes it, and the shared cultural schemas of the public servants tasked with its implementation. First, we contend that the effectiveness of top-down public policies enacted through laws and regulations relies on two key forms of validity: the legitimacy of the authority enacting the law—whether through constitutional or statutory frameworks—and the acceptability of the law’s content as something perceived as inevitable, fundamentally consensual, and recognized as a social obligation, reflecting the normative nature of the law. Second, we argue that top-down policies are more likely to be implemented effectively when their content aligns with the cultural meaning structures held by public servants. This alignment or congruence fosters a sense of ownership, increasing the likelihood of compliance with the law’s provisions. Finally, recognizing that a law’s legal validity and the propriety attributed to it by implementers may be only loosely coupled, we identify the conditions under which implementation is likely to result in conformity, customization, or ceremonial non-conformity. We conclude by discussing the practical and methodological implications of ensuring alignment between public servants’ cultural schemas and policy content, and we suggest empirical strategies to investigate this relationship.